The Crisis of Authority in Global Culture: An Interdisciplinary Analysis of Contemporary Shifts in Epistemology, Values, and Truth - John Massie; Yohanes Nduru; Herbin Simanjuntak (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2026)
The crisis of authority in global culture is a complex phenomenon reflecting a fundamental shift in how humans understand truth, values, and the sources of legitimacy of knowledge. This research focuses on the dynamics of epistemological change in global society influenced by digital technology, cultural relativism, and value pluralism. The main issue studied is how this crisis of authority influences the construction of truth and value systems in contemporary society, as well as its implications for social and spiritual life. The aim of this research is to develop an interdisciplinary analysis that integrates perspectives from philosophy, sociology, theology, and media studies in understanding this phenomenon. The method used is a qualitative approach based on systematic literature studies with a critical analysis of recent academic sources. The main findings indicate that the crisis of authority is characterized not only by the weakening of traditional institutions but also by the emergence of "alternative authorities" based on algorithms, public opinion, and subjective experience. This results in the fragmentation of truth, the relativization of values, and a crisis of epistemological legitimacy. The synthesis of this research confirms that the reconstruction of authority requires an integrative approach that combines rationality, ethics, and spiritual dimensions. In conclusion, the crisis of authority in global culture is not merely a challenge, but rather an opportunity to build a new epistemological paradigm that is more holistic, reflective, and rooted in transcendent values.